Modelling green urbanism in China. Issue 2 (25th September 2014) - Pow, C P; Neo, Harvey
<x xml:space="preserve">Abstract</x> This paper examines how the modelling of green urbanism is spatially manifested in flagship eco‐city projects such as the Sino‐Singapore Tianjin eco‐city (SSTE) project. As part of a multi‐scalar process that taps into a host of mobile policy networks and 'quick fix' urban policy solutions that circulate around the world, such eco‐flagship prestige projects serve as powerful sites for the convergence of the boundaries between the social and technical and are highly symbolic places charged with the formidable task of constructing purportedly new forms of ecological urban imagineering and socio‐ecological lifeworlds. But to the extent that these eco‐flagship projects are often underwritten by state‐business growth coalition and driven by (green) entrepreneurial objectives, these urban ecological spaces are also necessarily implicated in broader normative debates and the challenge of constructing sustainable and socially just urban futures. As David Harvey has pointed out, insofar as all environmental‐ecological arguments are arguments about society and, therefore, complex refractions of all sorts of struggles being waged on other realms, eco‐cities in China both reflect and embody the multiple contradictory tensions inherent in contemporary Chinese society.